Emergency Remote Teaching: The Challenges Associated with a Context of Second Language Instruction - MacKinnon, Gregory; MacLean, Tyler (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2023)
The pandemic of 2020 frequently necessitated that offshore school teachers continue their instruction of Chinese children in the online format rather than face-to-face back in China; a so-called emergency remote teaching response. A required change in pedagogy accompanied a range of challenges in an effort to offer quality education to English as a Second Language (ESL) students. During the fall 2020-2021 academic year, a sample of 25 teachers and 3 principals provided feedback on those inherent challenges in a mixed method study consisting of surveys, interviews, and focus groups. Factors that impacted the delivery were identified in broad categories of teacher lifestyle, hindrances with technology, teaching practice, and pedagogical support. The findings were unique in that 1) they were nested in a response to a difficult context as opposed to a carefully planned online instruction and 2) second language students constituted a different learning cohort. This work further adds to the literature by suggesting that cognitive load, self-regulation, and attentional literacy deserve careful consideration when contexts of ESL learning with technology are implicated.